Composite silicon negative electrode material and preparation method and application thereof
By covering the AB alloy layer in the silicon negative electrode material, the poor cycle stability problem caused by volume expansion of the silicon negative electrode during lithium embedding is solved, and high-rate performance, Coulomb efficiency and cycle stability are improved.
Patent Information
- Application Number
- CN202411757818.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-14
AI Technical Summary
The volume of the silicon negative electrode expands during lithium embedding, causing cracking during the circulation process, hindering the transmission of electrons and ions, thereby reducing the rate performance, Coulomb efficiency and cycling stability of the secondary battery.
A composite silicon negative electrode material is used, which includes silicon particles and an AB alloy layer coated on the surface of the silicon particles. Element A cannot form an alloy with Li, and element B can form an alloy with Li, which improves electron and ion conductivity through the alloy layer and provides mechanical stability.
During the cycle of the secondary battery, element B penetrates into the gaps of the negative electrode sheet, providing a good ion transmission channel, and element A serves as the electrode skeleton during the lithium-embedding/deliquefaction process to ensure the stability of the negative electrode sheet structure, improve the conductivity and electron transmission channels, significantly improving the rate performance, Coulomb efficiency and cycling stability of the secondary battery.
Smart Images

Figure CN119627072A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a composite silicon negative electrode material and a preparation method and application thereof. Background Art
[0002] Silicon as a negative electrode has a specific capacity of 3600mAh / g and a low voltage platform of ~0.4V. It has a wide range of raw materials and is low-cost, making it an ideal negative electrode material. However, the silicon negative electrode will undergo a volume expansion of ~400% during the lithium insertion process. The drastic volume change causes cracking during the cycle, hindering the transmission of electrons and ions. In addition, as the depth of lithium insertion decreases, the electronic conductivity and ionic conductivity of the silicon negative electrode will both decrease significantly, resulting in increased battery polarization and decreased capacity. Ultimately, the secondary battery exhibits problems such as low coulombic efficiency, poor cycle stability, and poor rate performance.
[0003] In addition, compared with traditional liquid lithium-ion batteries, all-solid-state batteries using inorganic solid electrolytes not only provide a wider operating temperature range, but also have higher safety and energy density. However, to obtain all-solid-state batteries with high safety and high energy density, it is necessary to develop high-capacity negative electrode materials. Summary of the invention
[0004] Based on this, it is necessary to provide a composite silicon negative electrode material and its preparation method and application to address the above problems. The composite silicon negative electrode material can greatly improve the rate performance, coulombic efficiency and cycle stability of the secondary battery while achieving a high-capacity negative electrode.
[0005] A composite silicon negative electrode material comprises silicon particles and an alloy layer coated on the surface of the silicon particles, wherein the chemical formula of the alloy layer is AB, wherein the A element is selected from metal elements that cannot form an alloy with Li, and the B element is selected from elements that can form an alloy with Li.
[0006] In one embodiment, the A element is selected from at least one of Fe and Cu; and / or the B element is selected from at least one of In, Sn and Bi.
[0007] In one of the embodiments, in the alloy layer, the atomic ratio of element A to element B is 5:95-95:5.
[0008] In one of the embodiments, in the composite silicon negative electrode material, the mass ratio of silicon particles to alloy layer is 0.3:0.7-0.95:0.05.
[0009] In one embodiment, the composite silicon negative electrode material has a core-shell structure.
[0010] A method for preparing the composite silicon negative electrode material comprises the following steps:
[0011] Coating a sacrificial agent on the surface of silicon particles to obtain a composite material, wherein the sacrificial agent is selected from at least one of zinc and magnesium;
[0012] The composite material is mixed with a metal salt solution to react, thereby obtaining a composite silicon negative electrode material, wherein the metal salt solution includes a salt of the A element and a salt of the B element.
[0013] In one of the embodiments, the mass ratio of the silicon particles to the sacrificial agent is 1:0.01-1:1.
[0014] A negative electrode sheet, wherein the negative electrode active material of the negative electrode sheet is the composite silicon negative electrode material.
[0015] A secondary battery uses the negative electrode sheet.
[0016] In one embodiment, the secondary battery is an all-solid-state battery.
[0017] In the composite silicon negative electrode material of the present invention, the alloy layer coated on the surface of the silicon particles has high electronic conductivity, ionic conductivity and suitable mechanical properties. When the composite silicon negative electrode material of the present invention is prepared into a negative electrode sheet and applied to a secondary battery, during the cycle of the secondary battery, the B element can penetrate into the gap of the negative electrode sheet to provide a good ion transmission channel for the negative electrode sheet, and the A element serves as an electrode skeleton in the process of lithium insertion / delithiation to ensure the stability of the negative electrode sheet structure, improve the electrical conductivity and provide a good electron transmission channel. Therefore, the composite silicon negative electrode material of the present invention can greatly improve the rate performance, coulomb efficiency and cycle stability of the secondary battery while achieving a high-capacity negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the conventional technology, the drawings required for use in the embodiments or the conventional technology descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 This is a SEM image of the composite silicon negative electrode material obtained in Example 7 of the present invention;
[0020] Figure 2 This is the SEM-EDS image of the composite silicon negative electrode material obtained in Example 7 of the present invention. DETAILED DESCRIPTION
[0021] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0023] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0024] In order to solve the problems of poor electron / ion transmission performance, large volume expansion and cracking during the cycle of silicon negative electrode, the composite silicon negative electrode material provided by the present invention includes silicon particles and an alloy layer coated on the surface of the silicon particles, and the chemical formula of the alloy layer is AB, wherein the A element is selected from metal elements that cannot form an alloy with Li, and the B element is selected from elements that can form an alloy with Li. Thus, the alloy layer formed by the A element and the B element has high electronic conductivity, ionic conductivity and suitable mechanical properties. Furthermore, when the composite silicon negative electrode material of the present invention is used to prepare a negative electrode sheet and applied to a secondary battery, during the cycle of the secondary battery, the B element can participate in the storage and release of lithium ions and has high ionic conductivity, providing a good ion transmission channel for the negative electrode. The A element serves as an electrode skeleton in the process of lithium insertion / de-lithiation, ensuring the stability of the negative electrode sheet structure, improving the conductivity and providing a good electron transmission channel.
[0025] Optionally, the A element is selected from at least one of Fe and Cu, which can be better used as an electron transmission channel, and the B element is selected from at least one of In, Sn, and Bi, which has better lithium ion transmission performance. Wherein, in the alloy layer, the atomic ratio of the A element and the B element is not limited. Preferably, the atomic ratio of the A element to the B element is 5:95-95:5, such as 5:95, 10:90, 15:85, 20:80, 25:75, 30:70, 35:65, 40:60, 45:55, 50:50, 55:45, 60:40, 65:35, 70:30, 75:25, 80:20, 85:15, 90:10, 95:5, etc., or a range composed of any two of these values, such as 25:75-75:25, 25:75-50:50, 50:50-75:25, etc.
[0026] Furthermore, the chemical formula of the alloy layer can be FeSn, FeSn2, FeIn, FeBi, CuIn, CuSn, CuBi, etc.
[0027] Optionally, in the composite silicon negative electrode material, the mass ratio of silicon particles to alloy layer is 0.3:0.7-0.95:0.05, for example, 0.3:0.7, 0.35:0.65, 0.4:0.6, 0.45:0.55, 0.5:0.5, 0.55:0.45, 0.6:0.4, 0.65:0.35, 0.7:0.3, 0.75:0.25, 0.8:0.2, 0.85:0.15, 0.9:0.1, 0.95:0.05, etc., or a range consisting of any two of these values, for example, 0.3:0.7-0.8:0.2, 0.3:0.7-0.5:0.5, 0.5:0.5-0.8:0.2, etc.
[0028] The present invention does not require the particle size of the silicon particles. Preferably, the particle size of the silicon particles is 40nm-2μm. In addition, it can be understood that when the alloy layer is coated on the surface of the silicon particles, it can be continuous coating, that is, the alloy layer completely coats the silicon particles, and the composite silicon negative electrode material has a core-shell structure, or it can be discontinuous coating, that is, some silicon particles can be exposed. Preferably, the alloy layer completely coats the silicon particles, and the composite silicon negative electrode material has a core-shell structure, which has a better effect.
[0029] The composite silicon negative electrode material of the present invention has a simple structure, and the alloy layer can be coated on the surface of silicon particles in different ways. Therefore, the present invention does not limit the preparation method of the composite silicon negative electrode material.
[0030] Specifically, the present invention also provides a method for preparing the composite silicon negative electrode material, comprising the following steps:
[0031] S1, coating a sacrificial agent on the surface of silicon particles to obtain a composite material, wherein the sacrificial agent is selected from at least one of zinc and magnesium;
[0032] S2, mixing the composite material with a metal salt solution to react, to obtain a composite silicon negative electrode material, wherein the metal salt solution includes a salt of element A and a salt of element B.
[0033] In the preparation method of the present invention, a sacrificial agent is first coated on the surface of silicon particles, and then an alloy layer is coated on the surface of the silicon particles by reduction replacement. Not only is the method simple, efficient, and has low costs such as equipment investment, but the alloy layer also has excellent coating effect and good uniformity, and can achieve complete coating to obtain a composite silicon negative electrode material with a core-shell structure.
[0034] Optionally, in the composite material of step S1, the mass ratio of the silicon particles to the sacrificial agent is preferably 1:0.01-1:1, for example, 1:0.01, 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5, 1:0.55, 1:0.6, 1:0.65, 1:0.7, 1:0.75, 1:0.8, 1:0.85, 1:0.9, 1:0.95, 1:1, etc., or a range consisting of any two of these values. Further preferably, the mass ratio of the silicon particles to the sacrificial agent is 1:0.05-1:1. With such an arrangement, a composite silicon negative electrode material with a core-shell structure can be better obtained.
[0035] In step S1, there are many ways to coat the sacrificial agent on the surface of the silicon particles, and the present invention is not limited to this. Since the ball milling process is simple and effective, as an example, in actual production, the sacrificial agent can be coated on the surface of the silicon particles by ball milling. The ball milling method can be high-energy ball milling, low-energy ball milling or ordinary ball milling. Among them, high-energy ball milling has a better dispersion effect. It is preferred to place the sacrificial agent in an inert atmosphere such as argon and nitrogen, and use high-energy ball milling to uniformly coat the sacrificial agent on the surface of the silicon particles to form a composite material.
[0036] In step S2, the metal salt solution includes a salt of element A and a salt of element B. Optionally, the salt of element A can be selected from at least one of chloride or its hydrate, nitrate or its hydrate, sulfate or its hydrate, acetylacetonate or its hydrate. For example, when element A is selected from Fe, it is selected from FeCl3, FeCl2·4H2O, Fe(acac)3(III), Fe(NO3)3·9H2O, FeSO4, Fe(OAc)2, etc. Similarly, the salt of element B is selected from at least one of chloride or its hydrate, nitrate or its hydrate, sulfate or its hydrate, acetylacetonate or its hydrate. Further, the salt of element A and the salt of element B are both selected from chlorides, such as indium trichloride, ferric chloride, tin tetrachloride, copper chloride, and bismuth chloride.
[0037] In addition, in the metal salt solution, the solvent is preferably deionized water and ethanol, the volume ratio of deionized water to ethanol is 1:1-1:10, and the total concentration of the salt of element A and the salt of element B is 0.05M-2M, for example, 0.05M, 0.1M, 0.2M, 0.3M, 0.4M, 0.5M, 0.6M, 0.7M, 0.8M, 0.9M, 1M, 1.1M, 1.2M, 1.3M, 1.4M, 1.5M, 1.6M, 1.7M, 1.8M, 1.9M, 2M, etc., or a range consisting of any two of these values, wherein the molar ratio of the salt of element A to the salt of element B can be calculated based on the required atomic ratio of element A to element B in the alloy layer.
[0038] Similarly, when the composite material is mixed with a metal salt solution for reaction, the molar ratio of the composite material to the metal salt solution can be calculated based on the required mass ratio of silicon particles to the alloy layer in the composite silicon negative electrode material.
[0039] The present invention also provides a negative electrode sheet, wherein the negative electrode active material of the negative electrode sheet is the composite silicon negative electrode material.
[0040] It can be understood that the negative electrode sheet generally includes a current collector and a negative electrode active coating attached to the surface of the current collector. The current collector is generally selected from copper foil, and the negative electrode active coating is generally made of composite silicon negative electrode material, binder, conductive agent, etc. in proportion.
[0041] The present invention also provides a secondary battery, wherein the secondary battery uses the negative electrode sheet, wherein the secondary battery may be a lithium-ion battery, an all-solid-state battery, or the like.
[0042] When the composite silicon negative electrode material of the present invention is prepared into a negative electrode sheet and applied to a secondary battery, during the cycle of the secondary battery, the B element can penetrate into the gap of the negative electrode sheet, providing a good electron and ion transmission channel for the negative electrode sheet, and the A element serves as the electrode skeleton during the lithium insertion / delithiation process, ensuring the stability of the negative electrode sheet structure and improving the conductivity. Therefore, the composite silicon negative electrode material of the present invention can greatly improve the rate performance, coulomb efficiency and cycle stability of the secondary battery while achieving a high-capacity negative electrode.
[0043] Furthermore, when the secondary battery is an all-solid-state battery and the composite silicon negative electrode material of the present invention is used to prepare a negative electrode sheet, an all-solid-state battery with high safety and high energy density can be obtained.
[0044] Hereinafter, the composite silicon negative electrode material and its preparation method and application will be further described through the following specific examples.
[0045] Example 1
[0046] 10 g of silicon particles with a particle size of 40 nm were selected and sealed with 8.9 g of zinc powder in a ball mill under an argon atmosphere, and high-energy ball milling was performed for 6 hours to obtain a composite material in which zinc uniformly wrapped silicon particles.
[0047] Deionized water and ethanol were prepared into a mixed solvent in a volume ratio of 1:5, and then 16.2 g of ferric chloride and 26.1 g of tin tetrachloride were dissolved in 200 mL of the mixed solvent to obtain a metal salt solution.
[0048] Then, the composite material obtained above was added to the metal salt solution, reacted under stirring at room temperature for 3 hours, and then centrifuged to obtain a precipitate. After washing with water and alcohol three times, it was placed in a vacuum drying oven at 80°C and completely dried to obtain a composite silicon negative electrode material.
[0049] The composite silicon negative electrode material obtained in this embodiment includes silicon particles and a FeSn alloy layer coated on the surface of the silicon particles, wherein the mass ratio of the silicon particles to the FeSn alloy layer is 0.3:0.7, and the atomic ratio of Fe and Sn in the FeSn alloy layer is 1:1.
[0050] Example 2
[0051] 10 g of silicon particles with a particle size of 1 μm were selected and sealed with 8.9 g of zinc powder in a ball mill under an argon atmosphere, and high-energy ball milling was performed for 6 hours to obtain a composite material in which zinc uniformly wrapped silicon particles.
[0052] Deionized water and ethanol were prepared into a mixed solvent in a volume ratio of 1:5, and then 16.2 g of ferric chloride and 26.1 g of tin tetrachloride were dissolved in 500 mL of the mixed solvent to obtain a metal salt solution.
[0053] Then, the composite material obtained above was added to the metal salt solution, reacted under stirring at room temperature for 3 hours, and then centrifuged to obtain a precipitate. After washing with water and alcohol three times, it was placed in a vacuum drying oven at 80°C and completely dried to obtain a composite silicon negative electrode material.
[0054] The composite silicon negative electrode material obtained in this embodiment includes silicon particles and a FeSn alloy layer coated on the surface of the silicon particles, wherein the mass ratio of the silicon particles to the FeSn alloy layer is 0.3:0.7, and the atomic ratio of Fe and Sn in the FeSn alloy layer is 1:1.
[0055] Example 3
[0056] 10 g of silicon particles with a particle size of 40 nm were selected, and sealed with 0.45 g of magnesium powder in a ball mill under an argon atmosphere, and high-energy ball milled for 6 hours to obtain a composite material in which zinc uniformly wrapped silicon particles.
[0057] Deionized water and ethanol were prepared into a mixed solvent in a volume ratio of 1:5, and then 3.24 g of ferric chloride and 5.22 g of tin tetrachloride were dissolved in 100 mL of the mixed solvent to obtain a metal salt solution.
[0058] Then, the composite material obtained above was added to the metal salt solution, reacted under stirring at room temperature for 3 hours, and then centrifuged to obtain a precipitate. After washing with water and alcohol three times, it was placed in a vacuum drying oven at 80°C and completely dried to obtain a composite silicon negative electrode material.
[0059] The composite silicon negative electrode material obtained in this embodiment includes silicon particles and a FeSn alloy layer coated on the surface of the silicon particles, wherein the mass ratio of the silicon particles to the FeSn alloy layer is 0.8:0.2, and the atomic ratio of Fe and Sn in the FeSn alloy layer is 1:1.
[0060] Example 4
[0061] 10 g of silicon particles with a particle size of 1 μm were selected, and sealed with 0.45 g of magnesium powder in a ball mill under an argon atmosphere, and high-energy ball milled for 6 hours to obtain a composite material in which zinc uniformly wrapped silicon particles.
[0062] Deionized water and ethanol were prepared into a mixed solvent in a volume ratio of 1:5, and then 3.24 g of ferric chloride and 5.22 g of tin tetrachloride were dissolved in 100 mL of the mixed solvent to obtain a metal salt solution.
[0063] Then, the composite material obtained above was added to the metal salt solution, reacted under stirring at room temperature for 3 hours, and then centrifuged to obtain a precipitate. After washing with water and alcohol three times, it was placed in a vacuum drying oven at 80°C and completely dried to obtain a composite silicon negative electrode material.
[0064] The composite silicon negative electrode material obtained in this embodiment includes silicon particles and a FeSn alloy layer coated on the surface of the silicon particles, wherein the mass ratio of the silicon particles to the FeSn alloy layer is 0.8:0.2, and the atomic ratio of Fe and Sn in the FeSn alloy layer is 1:1.
[0065] Example 5
[0066] 10 g of silicon particles with a particle size of 40 nm were selected, and sealed with 2.8 g of zinc powder in a ball mill under an argon atmosphere, and high-energy ball milled for 6 hours to obtain a composite material in which zinc uniformly wrapped silicon particles.
[0067] Deionized water and ethanol were prepared into a mixed solvent at a volume ratio of 1:5, and then 6.63 g of indium trichloride and 4.02 g of copper chloride were dissolved in 100 mL of the mixed solvent to obtain a metal salt solution.
[0068] Then, the composite material obtained above was added to the metal salt solution, reacted under stirring at room temperature for 3 hours, and then centrifuged to obtain a precipitate. After washing with water and alcohol three times, it was placed in a vacuum drying oven at 80°C and completely dried to obtain a composite silicon negative electrode material.
[0069] The composite silicon negative electrode material obtained in this embodiment includes silicon particles and a CuIn alloy layer coated on the surface of the silicon particles, wherein the mass ratio of the silicon particles to the CuIn alloy layer is 1:1, and the atomic ratio of Cu and In in the CuIn alloy layer is 1:1.
[0070] Example 6
[0071] 10 g of silicon particles with a particle size of 1 μm were selected and sealed with 2.8 g of zinc powder in a ball mill under an argon atmosphere, and high-energy ball milling was performed for 6 hours to obtain a composite material in which zinc uniformly wrapped silicon particles.
[0072] Deionized water and ethanol were prepared into a mixed solvent at a volume ratio of 1:5, and then 6.63 g of indium trichloride and 4.02 g of copper chloride were dissolved in 100 mL of the mixed solvent to obtain a metal salt solution.
[0073] Then, the composite material obtained above was added to the metal salt solution, reacted under stirring at room temperature for 3 hours, and then centrifuged to obtain a precipitate. After washing with water and alcohol three times, it was placed in a vacuum drying oven at 80°C and completely dried to obtain a composite silicon negative electrode material.
[0074] The composite silicon negative electrode material obtained in this embodiment includes silicon particles and a CuIn alloy layer coated on the surface of the silicon particles, wherein the mass ratio of the silicon particles to the CuIn alloy layer is 1:1, and the atomic ratio of Cu and In in the CuIn alloy layer is 1:1.
[0075] Example 7
[0076] 10 g of silicon particles with a particle size of 40 nm were selected, and sealed with 3.2 g of zinc powder in a ball mill under an argon atmosphere, and high-energy ball milled for 6 hours to obtain a composite material in which zinc uniformly wrapped silicon particles.
[0077] Deionized water and ethanol were prepared into a mixed solvent at a volume ratio of 1:5, and then 3.24 g of ferric chloride and 10.44 g of tin tetrachloride were dissolved in 200 mL of the mixed solvent to obtain a metal salt solution.
[0078] Then, the composite material obtained above was added to the metal salt solution, reacted under stirring at room temperature for 3 hours, and then centrifuged to obtain a precipitate. After washing with water and alcohol three times, it was placed in a vacuum drying oven at 80°C and completely dried to obtain a composite silicon negative electrode material.
[0079] The composite silicon negative electrode material obtained in this embodiment includes silicon particles and a FeSn2 alloy layer coated on the surface of the silicon particles, wherein the mass ratio of the silicon particles to the FeSn2 alloy layer is 1:1, and the atomic ratio of Fe and Sn in the FeSn2 alloy layer is 1:2.
[0080] In addition, from Figure 1 and Figure 2 It can be seen that Example 7 obtained a composite silicon negative electrode material, and the elements in the composite silicon negative electrode material were evenly distributed.
[0081] Example 8
[0082] 10 g of silicon particles with a particle size of 1 μm were selected and sealed with 3.2 g of zinc powder in a ball mill under an argon atmosphere, and high-energy ball milling was performed for 6 hours to obtain a composite material in which zinc uniformly wrapped silicon particles.
[0083] Deionized water and ethanol were prepared into a mixed solvent at a volume ratio of 1:5, and then 3.24 g of ferric chloride and 10.44 g of tin tetrachloride were dissolved in 200 mL of the mixed solvent to obtain a metal salt solution.
[0084] Then, the composite material obtained above was added to the metal salt solution, reacted under stirring at room temperature for 3 hours, and then centrifuged to obtain a precipitate. After washing with water and alcohol three times, it was placed in a vacuum drying oven at 80°C and completely dried to obtain a composite silicon negative electrode material.
[0085] The composite silicon negative electrode material obtained in this embodiment includes silicon particles and a FeSn2 alloy layer coated on the surface of the silicon particles, wherein the mass ratio of the silicon particles to the FeSn2 alloy layer is 1:1, and the atomic ratio of Fe and Sn in the FeSn2 alloy layer is 1:2.
[0086] Application Examples 1-8
[0087] 990 mg of the composite silicon negative electrode material obtained in Examples 1 to 8 above and 10 mg of polytetrafluoroethylene binder were dispersed in 2 ml of an organic solvent of N-methylpyrrolidone, stirred thoroughly, and then coated on a copper foil, and then vacuum dried at 100° C. to obtain a negative electrode sheet. The loading amount of silicon negative electrode in the negative electrode was 2 mg / cm 2 .
[0088] Then, high-voltage lithium cobalt oxide and solid electrolyte lithium phosphorus sulfur chloride (Li6PS5Cl) were ground evenly in a mass ratio of 7:3 and mixed as the positive electrode. Lithium phosphorus sulfur chloride was used as the solid electrolyte and assembled with the above-obtained negative electrode sheet to assemble an all-solid-state battery. The N / P of the battery was controlled to be ~1.1, and the cycle performance test was carried out in the range of 2.5V-4.4V. The results are shown in Table 1.
[0089] Application Comparative Example 1
[0090] The difference between the comparative application example 1 and the example application is that the composite silicon negative electrode material is replaced with 40 nm silicon particles.
[0091] Application Comparative Example 2
[0092] The difference between the comparative application example 2 and the example application is that the composite silicon negative electrode material is replaced with 1 μm silicon particles.
[0093] Table 1
[0094]
[0095] As can be seen from Table 1, when pure silicon is used as the negative electrode material, at a rate of 2C, the capacity retention rates of nano-silicon and micro-silicon are 36% and 18% respectively, the capacity retention rates after 100 cycles are 65% and 58%, and the average coulombic efficiency is 99.56% and 99.35%. After being coated with the alloy layer of the present invention, although the capacity of the composite silicon negative electrode material has decreased, the capacity retention rate and cycle stability at high rates have been improved, and the average coulombic efficiency has also been improved to 99.9%. In Example 4, a specific capacity of up to 2859 mAh / g is achieved, and a capacity retention rate of 86% is maintained for 100 cycles. In Example 5, a high rate performance of 72% at 2C is achieved, and it also has a high specific capacity of 2056 mAh / g.
[0096] Therefore, the composite silicon negative electrode material of the present invention can significantly improve the rate performance, coulombic efficiency and cycle stability of the secondary battery while achieving a high-capacity negative electrode, and a composite silicon negative electrode material with high capacity or good rate can be selected according to the application scenario.
[0097] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0098] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A composite silicon negative electrode material, characterized in that: It comprises silicon particles and an alloy layer coated on the surface of the silicon particles, wherein the chemical formula of the alloy layer is AB, wherein the A element is selected from metal elements that cannot form an alloy with Li, and the B element is selected from elements that can form an alloy with Li.
2. The composite silicon negative electrode material according to claim 1, characterized in that: The A element is selected from at least one of Fe and Cu; and / or the B element is selected from at least one of In, Sn and Bi.
3. The composite silicon negative electrode material according to claim 1, characterized in that: In the alloy layer, the atomic ratio of element A to element B is 5:95-95:
5.
4. The composite silicon negative electrode material according to claim 1, characterized in that: In the composite silicon negative electrode material, the mass ratio of silicon particles to alloy layers is 0.3:0.7-0.95:0.
05.
5. The composite silicon negative electrode material according to claim 1, characterized in that: The composite silicon negative electrode material has a core-shell structure.
6. A method for preparing the composite silicon negative electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Coating a sacrificial agent on the surface of silicon particles to obtain a composite material, wherein the sacrificial agent is selected from at least one of zinc and magnesium; The composite material is mixed with a metal salt solution to react, thereby obtaining a composite silicon negative electrode material, wherein the metal salt solution includes a salt of the A element and a salt of the B element.
7. The method for preparing the composite silicon negative electrode material according to claim 6, characterized in that: The mass ratio of the silicon particles to the sacrificial agent is 1:0.01-1:
1.
8. A negative electrode sheet, characterized in that: The negative electrode active material of the negative electrode sheet is the composite silicon negative electrode material according to any one of claims 1 to 5.
9. A secondary battery, characterized in that: The secondary battery uses the negative electrode sheet according to claim 8.
10. The secondary battery according to claim 9, characterized in that: The secondary battery is an all-solid-state battery.